The Incorporation of Customary Water Rules under the Ethiopian Formal Water Governance System: Clash of Values between Commodification and Preservation - Degu, Temesgen (Indonesia Law Reform Journal, 2023)
Customary water rules need to be adequately incorporated into the Ethiopian formal water governance system despite their significance for ensuring sustainable and equitable utilization of scarce water resources. This research, using the textual analysis method and employing the theory of institutional incongruence, seeks to explore the extent of recognition of customary water rules under the formal water governance system of Ethiopia. The article argues that there needs to be more recognition of customary water rules under the Ethiopian formal water governance system, which has led to conflicts, inefficiencies, and unsustainable use of water resources. This is due to the value clash between the formal water rules built on the notion of water as a resource for commodification and customary water rules that see water as a sacred and communal part of communities' sociocultural and ecological being. As a result of this value clash, customary water rules, however important sustainability tenets they might lend, are only easily amenable to the formal water governance framework in the first place, questioning its basic foundations. Strategies such as incorporating ecosystems-based approaches, recognizing and integrating traditional knowledge, and promoting participatory decision-making processes can assist in bridging the gaps between commodification and preservation values. This, in turn, requires and largely depends on finding the right balance between economic development and environmental sustainability. This entails a fundamental reconsideration of the very goals of the Ethiopian water resources management policy, proclamation and regulation.